Development of an Ignition Coil Integrated System to Monitor the Spark Plugs Wear - Fernandes, Filipa Rodrigues Filipe (2019)
Automotive industry is undergoing significant changes to answer new emission limits and cost restrictions. These lead to unfavourable operating conditions for the components (including spark plugs and ignition coils): overheating, higher pressures, downsizing and leaner air/fuel mixtures. Consequently, the ignition coil integrated system is being asked for stronger and multiple sparks and longer burning times. In response, rare precious metals (iridium, platinum, tungsten) must be utilized, resulting in a cost increase thereof. Hence, it is a main interest to monitor these high quality components. In this work, Paschen Law is used to find a relation between the electrodes gap (ultimately related to wear conditions) and breakdown voltage. Thereby, this thesis is mainly focused on developing a method to monitor the referred voltage. In a transistor-ized coil ignition (TCI) system, the microcontroller can measure a time which is directly proportional to the breakdown voltage. That information is collected coil-internally and communicated to the ECU. The latter carries out statistical data analysis along with re-al-time pressure, load and speed data. After laboratory and car tests, it was proved that the secondary current sensing circuit may also serve as a breakdown voltage sensor, eliminating the need for any cost increase rather than development costs concerning mass production of ignition coils.